2023
DOI: 10.1038/s41398-023-02472-9
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionarily recent retrotransposons contribute to schizophrenia

Abstract: Transposable elements (TEs) are mobile genetic elements that constitute half of the human genome. Recent studies suggest that polymorphic non-reference TEs (nrTEs) may contribute to cognitive diseases, such as schizophrenia, through a cis-regulatory effect. The aim of this work is to identify sets of nrTEs putatively linked to an increased risk of developing schizophrenia. To do so, we inspected the nrTE content of genomes from the dorsolateral prefrontal cortex of schizophrenic and control individuals and ide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…These changes can occur in both coding and non-coding regions and can lead to significant changes in gene expression, function, and underlying phenotype [ 70 , 71 , 72 , 73 ]. SVs are a major contributor to the diversity of the human genome, and they can cause disease when they alter important regulatory elements or disrupt essential genes [ 74 , 75 ]. The vast majority of SVs are not found in the reference genome, so their detection and characterization are challenging [ 76 , 77 , 78 , 79 ].…”
Section: Describing the Repertoire Of Structural Variationmentioning
confidence: 99%
“…These changes can occur in both coding and non-coding regions and can lead to significant changes in gene expression, function, and underlying phenotype [ 70 , 71 , 72 , 73 ]. SVs are a major contributor to the diversity of the human genome, and they can cause disease when they alter important regulatory elements or disrupt essential genes [ 74 , 75 ]. The vast majority of SVs are not found in the reference genome, so their detection and characterization are challenging [ 76 , 77 , 78 , 79 ].…”
Section: Describing the Repertoire Of Structural Variationmentioning
confidence: 99%
“…Moreover, complex phenotypes involving diverse gene regulation can also be attributed to TE polymorphism. Recently, Modenini et al investigated human polymorphic non-reference TEs (nrTEs) and identified evolutionarily young nrTE candidates that may potentially increase the risk of schizophrenia [128]. However, the underlying mechanisms remain elusive without functional validations.…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%